An Assessment of Antihypertensive Drug Utilization Patterns and Adherence to JNC-7 Guidelines in South Indian Tertiary Care Teaching Hospital - Surapaneni, Sai Sujana; Nasrin Arifa, Shaik; Venigalla, Sahithi; Peter PL, Haroled; Pingili, Ravindrababu; Reddy Challa, Siva (Indian Journal of Pharmacy Practice)
Objective: The objective of this study was to assess the adherence of antihypertensive medication to Joint National Committee (JNC)-7 and drug-drug interactions between drugs prescribed for patients with hypertension and its co-morbidities in a south Indian tertiary care teaching hospital. Methods: A total of 200 hypertension prescriptions were collected in a prospective observational study from February 2014 to July 2014. Medication adherence was assessed by comparing with the JNC-7 guidelines and drug-drug interactions were reported after checking in standard databases for their mechanism of interaction. Results: The average age was 58.8 ± 2.40 years (males) and 53.7 ± 2.3 years (females). Stage 1 hypertension (36%, males; 35.2%, females) was most predominant than stage 2 hypertension (29.33%, males; 30.4%, females) and hypertension emergency (25.33%, males; 23.2%, females). Diabetes mellitus (19%, males; 45%, females) and cardiovascular diseases (27%, males; 36%, females) are the most common co-morbidities in hypertension patients followed by renal diseases. Calcium channel blockers (9.4%) are most widely prescribed drugs followed by angiotensin receptor blockers (6.9%) and diuretics (6.9%) in monotherapy. Angiotensin receptor blocker + diuretic combination (4.9%) was mostly used in two drug combination therapy. The overall rate of adherence was 15.6% (Pre hypertension); 37.87% (Stage 1 hypertension); 26.21% (Stage 2 hypertension) and 50% (Hypertension emergency). In the present study, the major drug interaction was digoxin and angiotensin receptor blockers (11.9%) followed by the clopidogrel + calcium channel blockers combination (9.5%). Conclusion: Results reveal that optimal medication adherence to JNC-7 guidelines was not observed in the prescriptions.
Keywords: Hypertension; Joint National Committee (JNC); Medication adherence; Drug-Drug interactions; Stroke